2017
DOI: 10.1037/edu0000118
|View full text |Cite
|
Sign up to set email alerts
|

Individual and class norms differentially predict proactive and reactive aggression: A functional analysis.

Abstract: Theory and research using a social-information processing framework indicate that reward-focused (proactive) aggression has different social consequences than defense-focused (reactive) aggression. Students use norms that identify expected and socially approved behaviors as guides to their own actions. Differences in social-cognitive processing characteristics and social status linked to each type of aggression may increase the relevance of some normative sources relative to others. This study fills a gap in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Supporting the first pattern, Farrell, Henry, Mays, and Schoeny (2011) showed that deviant behavior was elevated in peer groups in which the collective normative acceptance of deviant behavior was high. Longitudinally, the overall level of reactive aggression in the classroom was shown to predict higher levels of individual reactive and proactive aggressions 6 months later (Frey, Higheagle Strong, & Onyewuenyi, 2016).…”
Section: Peer Influences On Deviant Behaviormentioning
confidence: 99%
“…Supporting the first pattern, Farrell, Henry, Mays, and Schoeny (2011) showed that deviant behavior was elevated in peer groups in which the collective normative acceptance of deviant behavior was high. Longitudinally, the overall level of reactive aggression in the classroom was shown to predict higher levels of individual reactive and proactive aggressions 6 months later (Frey, Higheagle Strong, & Onyewuenyi, 2016).…”
Section: Peer Influences On Deviant Behaviormentioning
confidence: 99%
“…Forms refer to the type of behavior intending to harm the victim: aggressive conduct may involve a direct confrontation with others (e.g., intimidating, pushing, hitting, threatening, or insulting-overt aggression) or, on the contrary, may imply damaging the social reputation or social status of victims and isolate them from their friends, going so far as to use their group of peers (e.g., social exclusion, social rejection, or spreading rumors; Xie et al, 2002; Little et al, 2003; Juvonen and Graham, 2014) With regard to functions, i.e., the aggression's purpose, this type of conduct has been found to be due possibly to reacting to real or perceived damage -reactive aggression-, or a means to obtain a desired result -proactive aggression- (Coie and Dodge, 1998). While reactive aggression is fundamentally emotional and impulsive (Card and Little, 2006), proactive aggression implies an intentional behavior directed toward fulfilling a desired goal and, therefore, depends on an evaluation of the consequences (Fontaine and Dodge, 2006; Frey et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Previous study shows that sense of control is signi cantly related to life history strategies (Dodge, 1990), and the uctuating changes and levels of the sense of control are the result of internal trade-offs in the individual's life history. Fast strategists often maintain their sense of control through irrational behaviors such as current squandering and instant grati cation (Wright, 2013), while slow strategists tend to maintain and improve their sense of control by reducing risky behaviors (Frey, 2017).…”
Section: Sense Of Control As a Mediatormentioning
confidence: 99%